2021
DOI: 10.3390/foods10030492
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Berberis vulgaris Anthocyanins into Nanoliposome Composed of Rapeseed Lecithin: A Comprehensive Study on Physicochemical Characteristics and Biocompatibility

Abstract: In the present study, nanoliposomes composed of rapeseed lecithin were used for the encapsulation of anthocyanin compounds (AC). The nanoliposomes were prepared using hydration and ultrasound combined method, and the effect of AC concentration (4.5, 6.75, 9% w/w) on the characteristics of nanoliposomes including particle size, polydispersity index (PDI), zeta potential, and the encapsulation efficiency (EE) of nanoliposomes with and without AC were studied. The results suggested the fabricated nanoliposomes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
(61 reference statements)
1
6
0
1
Order By: Relevance
“…In the early stage of storage, the aggregation of nanoliposomes may cause little increase the PDI, while the PDI of the later supersaturated nanoliposomes may decrease due to the precipitation of part of naringenin. Similar to Homayoonfal et al’s study of the stability of anthocyanin compound loaded nanoliposomes at 37 °C, there were no significant difference in the parameters of PDI and ζ-potential after one month of storage, but the particle diameter and encapsulation efficiency significantly increased and decreased, respectively [ 36 ]. Although the instability mechanism is not yet clear, it may be because of the aggregation and leakage of nanoliposomes and chemical degradation of naringenin in nanoliposomes solutions, which results in color changes or precipitation at high store temperature [ 20 , 37 , 38 ].…”
Section: Resultssupporting
confidence: 55%
“…In the early stage of storage, the aggregation of nanoliposomes may cause little increase the PDI, while the PDI of the later supersaturated nanoliposomes may decrease due to the precipitation of part of naringenin. Similar to Homayoonfal et al’s study of the stability of anthocyanin compound loaded nanoliposomes at 37 °C, there were no significant difference in the parameters of PDI and ζ-potential after one month of storage, but the particle diameter and encapsulation efficiency significantly increased and decreased, respectively [ 36 ]. Although the instability mechanism is not yet clear, it may be because of the aggregation and leakage of nanoliposomes and chemical degradation of naringenin in nanoliposomes solutions, which results in color changes or precipitation at high store temperature [ 20 , 37 , 38 ].…”
Section: Resultssupporting
confidence: 55%
“…Among them, carbohydrates derived from alginate and chitosan, natural gums, and protein derivatives are the most popular [164,177]. They are very effective in encapsulating anthocyanins and contribute greatly to shifting the flavylium cation structure, protecting them from negative environmental effects, thus promoting their stability in the gastrointestinal tract and increasing their bioavailability [20,160,178]. Thus, several studies have already shown that encapsulation of anthocyanins with chitosan and derivatives can improve their physical and oxidative stability, preserve their antioxidant activity, and promote a slower degradation during simulated gastrointestinal digestion and environmental storage [22,27,164,179,180].…”
Section: Anthocyanins In Nano-delivery Systemsmentioning
confidence: 99%
“…In addition, as once they are composed of an aqueous core and a spherical hydrophobic shell, they can transport hydrophilic, hydrophobic, and amphiphilic molecules as well as ease cross the blood-brain barrier [173]. Regarding their encapsulation with anthocyanins, Homayoonfal and colleagues [178] have shown that they can enhance the antioxidant capacity of anthocyanins in a very remarkable and effective manner, as well as increase the metabolite activity and replication of human mesenchymal MSC and fibroblast FBL stem cells, at concentrations of 0.5 mg/mL and 10.4 µg/mL, respectively, after a one-week of treatment. Moreover, it has been also reported that there is a positive correlation between the size of nanoliposome particles and the encapsulation efficiency [161].…”
Section: Liposome Coatingsmentioning
confidence: 99%
“…A encapsulação em lipossomas de antocianinas extraídas de arônia se provou eficiente para aumentar a estabilidade, atividade antioxidante e permeabilidade na pele (LEE; NA, 2020). Lipossomas compostos de lecitina de colza foram utilizados para encapsular antocianinas extraídas de Berberis vulgaris, formando nanopartículas compatíveis com células mesenquimais humanas e fibroblastos (HOMAYOONFAL et al, 2021). Outros trabalhos reportam melhoria da estabilidade e capacidade antioxidante de antocianina após passagem por fluido gastrointestinal simulado (FAN et al, 2021;SHISHIR et al, 2020;.…”
Section: Encapsulamento De Compostos Bioativos Em Lipossomasunclassified